Creative Process Of Janger Dance “Nusantara Mahardika” - Haryati, Ni Made; Hartini, Ni Putu; Kandiraras, Tudhy Putri Apyutea (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2023)
The creation of this Janger Dance refers to the concept of a dance based on the moral message contained in the philosophical meaning of Bhineka Tunggal Ika. One of the efforts to cultivate Bhineka Tunggal Ika is to incorporate this philosophy into a dance piece that will eventually serve as a tool for expressing the values and meaning of unifying the nation.Janger is performed by 16 dancers, 8 of whom are female and 8 of whom are male. As a social dance, Janger is expected to be able to encourage the younger generation to comprehend and implement the philosophy of Bhineka Tunggal Ika by utilizing the creative process in its creation effectively. The creation of the Janger dance "Nusantara Mahardika" implements the method of artistic creation described by Alma M. Hawkins in his book "Creating Through Dance.", which was translated by Y. Sumandiyo Hadi (2003) in Mencipta Lewat Tari. According to Alma M. Hawkins, the stages of art creation consist of exploration, improvisation, and forming."